Terjebak Dalam Ketakutan: Kualitatif Tinjauan Sistematis Kecemasan Sosial pada Kehidupan Remaja - Bahri, Marlistiani; Kholidin, Farid Imam (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2024)
Social anxiety in adolescents is becoming an increasingly relevant and urgent issue as adolescence is a critical period of physical, mental, social and emotional development. This study aims to understand social anxiety in adolescents by reviewing the prevalence, causes, effects and indicators of social anxiety. A qualitative systematic review method was used to analyse 10 journal articles from 2019 to 2024, which were searched using Google Scholar and Harzing publish or perish applications. The results showed that levels of social anxiety varied, with a higher prevalence in adolescent girls. Factors such as social media use, lack of confidence, openness and substance abuse were found to have a significant impact on social anxiety levels. The consequences of social anxiety include reduced academic performance, peer relationship problems, social avoidance and risk of depression. This research highlights the importance of a deeper understanding of the causal factors and effects of social anxiety in order to develop effective interventions. The results of this study should not only add to academic knowledge, but also make a practical contribution to efforts to improve the quality of life of adolescents with social anxiety problems. The limitations of this study include the limited number of articles, so it is hoped that future research will be able to analyse the results of this study.